Advances and trends in engineering sciences and technologies : proceedings of the International Conference on Engineering Sciences and Technologies, 29 June-1 July 2016, High Tatras Mountains, Tatranské Matliare, Slovak Republic /: proceedings of the International Conference on Engineering Sciences and Technologies, 29 June-1 July 2016, High Tatras Mountains, Tatranské Matliare, Slovak Republic. (2016) - Unknown
No abstract available